PENINGKATAN KETERAMPILAN MEMBUAT TAMPILAN DIGITAL MENGGUNAKAN 7 SEGMEN DAN LCD BAGI SISWA SMK N 1 PAINAN DAN SMK N 1 KOTO XI TARUSAN - Habibullah Habibullah; Asnil Asnil; Ali Basrah Pulungan; Juli Sardi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
SMKN 1Painan and SMKN 1 Koto XI Tarusan is a school of many Vocational Schools whose activities refer to the preparation of students to enter employment and the development of professional attitudes. Based on the results of surveys and interviews conducted by the implementation team with the SMKN 1 Painan and SMKN 1 Koto XI Tarusan, data was obtained that they really needed skills in the field of Digital Engineering. The purpose of this activity is to improve students' skills in understanding digital electronic circuits as a provision for entering employment. The method used is a lecture method on digital engineering material and direct practice on how to make digital electronic circuits. This activity was carried out at SMKN 1 Painan which lasted for 2 days. The results obtained from this activity are in the form of digital electronic circuits in the form of a 1 digit up counter series of 10 units and an increase in students' skills in making and understanding the workings of the circuit that has been made.